The State, Religion, and Social Media: A Critical Review of Islamic Counseling Policy in Indonesia - Hidayati, Lili (Indonesian Academy of Social and Religious Research (IASRR), 2025)
Advances in information technology, particularly the internet and social media, have significantly changed communication and interaction within society. The ease of accessing information has made the global community resemble a global village. Digital technology has both positive and negative impacts that must be addressed wisely. Religious counsellors, as the frontline of the Ministry of Religion, are required to transform. Directorate General of Islamic Education Decision No. 1172 of 2024 provides guidelines for the implementation of religious counselling on social media. This study explores the opportunities, challenges, and alternative solutions for the implementation of the aforementioned decision. Using a descriptive quantitative research method, it can be concluded that religious counsellors must transform themselves to be willing and able to use social media for preaching and counselling. The role of digital technology brings benefits in various aspects, including religious counselling; however, social media must be used wisely so that religious counselling can run smoothly and provide benefits to society at large